FUNGSI BIAYA PABRIK GULA DI JAWA - Noer Soetrisno (Faculty of Economics and Business, Universitas Gadjah Mada, 1986)
This article deals with the cost function on sugar industry operated in Jawa Island. The results indicate that management on production rate becomes uncontrollabe after the TRI system is implemented. Besides, increasing returns to scale effect occurs implying that small sugar industries need development policy. Finally, synergy between small industries suggests an important mean to reach efficiency rate on the studied field.